Is re-Rex shunt a better choice for patients with failed Rex shunt? - Wen, Zhe; Wang, Jieqin; Yang, Chao; Liu, Tao; Liang, Qifeng; Liang, Jiankun; Ning, Yu; You, Fuyu; Bai, Xiaoling; Hong, Miao (Frontiers in Pediatrics, 2023)
Purpose To review our single-center surgical outcomes of redo operations after failed Rex shunt procedures. Methods From September 2017 to October 2021, a total of 20 patients (11 males, 9 females; median age: 8.6 years) with Rex shunt occlusions were admitted to our hospital. Two of these patients were previously operated on in our hospital, and the remaining 18 were from other centers. All patients underwent repeat operations after detailed preoperative evaluations. Results Preoperative wedged hepatic vein portography (WHVP) was conducted for 18 patients. Thirteen patients exhibited well-developed Rex recessus and intrahepatic portal vein during WHPV examination, consistent with the intraoperative exploration results. Fifteen patients (75%, 15/20) underwent redo-Rex shunt, four underwent Warren shunt and one underwent devascularization surgery. During the redo-Rex shunt operations, the left internal jugular veins (IJV) were used as bypass grafts in 11 patients; the intra-abdominal veins were used in 4 patients. The patients were followed up for 12–59 months (mean, 24.8 months). After redo Rex shunts, the grafts were patent in 14 patients (93.3%, 14/15), but 1 graft had thrombosis (6.7%, 1/15). Three patients suffered from postoperative anastomotic stenosis, and all of the stenosis was relieved with balloon dilatations. After re-Rex shunts, esophageal varices and spleen size were substantially reduced, and the platelet count significantly increased. Postoperative graft thrombosis was found in 1 patient after Warren shunt (1/4, 25%), and there was no graft stenosis. Compared with Warren surgery, patients who underwent re-Rex shunt had a significantly higher rate of platelet increase. Conclusions Redo-rex shunts can be finished in most patients with failed Rex shunts. Re-Rex shunt is a preferred surgical choice after a failed Rex shunt when a good bypass graft is available, and the surgical success rate can reach more than 90%. A suitable bypass graft is essential for a successful redo Rex shunt. Preoperative WHVP is recommended for the design of a redo surgical plan preoperatively.